Epigenetic regulation of p21cip1/waf1 in human cancer - Ocker, Matthias; Al Bitar, Samar; Monteiro, Ana; Gali-Muhtasib, Hala; Schneider-Stock, Regine (Cancers, 2019)
p21cip1/waf1 is a central regulator of cell cycle control and survival. While mutations are rare, it is commonly dysregulated in several human cancers due to epigenetic mechanisms influencing its transcriptional control. These mechanisms include promoter hypermethylation as well as additional pathways such as histone acetylation or methylation. The epigenetic regulators include writers, such as DNA methyltransferases (DNMTs); histone acetyltransferases (HATs) and histone lysine methyltransferases; erasers, such as histone deacetylases (HDACs); histone lysine demethylases [e.g., the Lysine Demethylase (KDM) family]; DNA hydroxylases; readers, such as the methyl-CpG-binding proteins (MBPs); and bromodomain-containing proteins, including the bromo-and extraterminal domain (BET) family. We further discuss the roles that long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) play in the epigenetic control of p21cip1/waf1 expression and its function in human cancers.
CRIS-Team Scopus Importer:2019-10-22
Keywords: DNA methylation; Epigenetic eraser; Epigenetic reader; Epigenetic writer; Histone acetylation; Histone methylation; LncRNA; MiRNA; P21

The activating transcription factor 2: an influencer of cancer progression - Hübner, Kerstin; Prochazka, Jan; Monteiro, Ana; Mahadevan, Vijayalakshmi; Schneider-Stock, Regine (Mutagenesis, 2019)
In contrast to the continuous increase in survival rates for many cancer entities, colorectal cancer (CRC) and pancreatic cancer are predicted to be ranked among the top 3 cancer-related deaths in the European Union by 2025. Especially, fighting metastasis still constitutes an obstacle to be overcome in CRC and pancreatic cancer. As described by Fearon and Vogelstein, the development of CRC is based on sequential mutations leading to the activation of proto-oncogenes and the inactivation of tumour suppressor genes. In pancreatic cancer, genetic alterations also attribute to tumour development and progression. Recent findings have identified new potentially important transcription factors in CRC, among those the activating transcription factor 2 (ATF2). ATF2 is a basic leucine zipper protein and is involved in physiological and developmental processes, as well as in tumorigenesis. The mutation burden of ATF2 in CRC and pancreatic cancer is rather negligible; however, previous studies in other tumours indicated that ATF2 expression level and subcellular localisation impact tumour progression and patient prognosis. In a tissue- and stimulus-dependent manner, ATF2 is activated by upstream kinases, dimerises and induces target gene expression. Dependent on its dimerisation partner, ATF2 homodimers or heterodimers bind to cAMP-response elements or activator protein 1 consensus motifs. Pioneering work has been performed in melanoma in which the dual role of ATF2 is best understood. Even though there is increasing interest in ATF2 recently, only little is known about its involvement in CRC and pancreatic cancer. In this review, we summarise the current understanding of the underestimated 'cancer gene chameleon' ATF2 in apoptosis, epithelial-to-mesenchymal transition and microRNA regulation and highlight its functions in CRC and pancreatic cancer. We further provide a novel ATF2 3D structure with key phosphorylation sites and an updated overview of all so-far available mouse models to study ATF2 in vivo.
CRIS-Team WoS Importer:2020-02-07